Advancements in deep eutectic solvent-based membranes for the extraction, separation, and preconcentration of organic compounds - Abdullah Sani, Nur Fitrah; Ramadhan, Rico; Yahaya, Noorfatimah; Sheikh Ghadzi, Siti Maisharah; Mohamed, Ahmad Husaini; Kamaruzaman, Sazlinda; Wan Ibrahim, Wan Nazihah; Mohamad Hanapi, Nor Suhaila; Mohamad Zain, Nur Nadhirah (Elsevier B.V., 2025)
Deep eutectic solvents have emerged as a sustainable alternative to conventional organic solvents and ionic liquids, offering advantages such as low toxicity, biodegradability, and cost-effectiveness. Their integration into membrane-based systems has revolutionized extraction, separation, and preconcentration techniques, particularly for organic compounds in aqueous matrices. This review provides a comprehensive analysis of deep eutectic solvent-based membranes, focusing on their classifications, preparation methods, and fabrication strategies. The application of different types of deep eutectic solvent-based membranes is critically evaluated. Special attention is given to the optimization of extraction parameters, and mechanisms governing analyte-membrane interactions. While deep eutectic solvent-based membranes demonstrate significant potential for enhanced selectivity, enrichment, and recovery, challenges such as membrane stability, scalability, and compatibility with analytical instrumentation remain. Addressing these limitations through advanced material engineering and process optimization will be crucial for broader adoption. This review highlights recent advancements, identifies research gaps, and outlines future perspectives to enhance the applicability of deep eutectic solvent-based membranes in analytical and environmental sciences.